The beneficial effects of Lactobacillus brevis FZU0713-fermented Laminaria japonica on lipid metabolism and intestinal microbiota in hyperlipidemic rats fed with a high-fat diet. Issue 16 (7th July 2021) - Zhang, Qing; Fan, Xiao-Yun; Cao, Ying-Jia; Zheng, Ting-Ting; Cheng, Wen-Jian; Chen, Li-Jiao; Lv, Xu-Cong; Ni, Li; Rao, Ping-Fan; Liang, Peng
Abstract : The beneficial effects of the oral administration of  Lactobacillus brevis  FZU0713-fermented Laminaria japonica  (FLJ) on lipid metabolism and intestinal microbiota. Abstract : This study aimed to investigate the beneficial effects of the oral administration of Lactobacillus brevis FZU0713-fermented Laminaria japonica (FLJ) on lipid metabolism and intestinal microbiota in hyperlipidemic rats fed with a high-fat diet (HFD). The results demonstrated that the oral administration of FLJ significantly inhibited obesity and improved the serum and hepatic biochemical parameters in HFD-fed rats. Histopathological results also indicated that FLJ intervention could significantly reduce the accumulation of lipid droplets in the liver induced by HFD feeding. Furthermore, FLJ intervention up-regulated the fecal short-chain fatty acid (SCFA) levels (mainly acetate, propionate and isobutyrate) in HFD-fed rats. Intestinal microbiota profiling by 16S rRNA gene sequencing revealed that FLJ intervention increased the relative abundance of Akkermansia, Collinsella, Ruminococcaceae _UCG-013, Defluviitaleaceae _UCG-011, Intestinimonas, Actinomyces and Tyzzerella, but decreased the abundance of Flavonifractor, Collinsella, Sporosarcina and Lacticigenium . Based on Spearman's correlation, the fecal levels of TC, TG, acetic acid and butyric acid were positively correlated with the relative abundance of Akkermansia and Ruminococcaceae _NK4A214, but negatively correlated with the relative amount of Flavonifractor and Collinsella . The metabolic function of intestinal microbiota predicted by PICRUSt analysis of 16S rRNA gene sequences demonstrated that primary and secondary bile acid biosyntheses, fatty acid biosynthesis, taurine and hypotaurine metabolism, arachidonic acid metabolism, glycolysis/gluconeogenesis, etc . were significantly down-regulated after 8 weeks of FLJ intervention. Additionally, FLJ intervention significantly regulated the hepatic mRNA levels (including BSEP, CYP7A1, LDLR, HMGCR, CD36 and SREBP1-C ) involved in lipid metabolism and bile acid homeostasis. In conclusion, these findings support the possibility that Laminaria japonica fermented with probiotic Lactobacillus has the potential to reduce the disturbance of lipid metabolism by regulating intestinal microflora and liver gene expression profiles, so it can be employed as a potential functional food to prevent hyperlipidemia.